Urban Transformation in the Context of Rail Transport Development: The Case of a Newly Built Railway Line in Gdańsk (Poland) - Marcin Połom; Maciej Tarkowski; Krystian Puzdrakiewicz (Journal of Advanced Transportation)
Development of railway transport systems is perceived as one of the most effective ways of shaping sustainable urban transportation. However, railway transportation systems can only compete with individual means of transportation when having properly developed infrastructure, especially in terms of the train stops accessibility. The main objective of this article is to discuss mutual relations between operation of a newly built railway line and spatial changes taking place in its closest vicinity which determine the accessibility to it. The research methods included the GIS tools, direct measurements of passenger exchange, and public opinion poll among the passengers taking the new line. The research area was the city of Gdańsk, one of the largest cities in Poland, where transportation problems are cumulating as a result of the urban sprawl. The new railway was opened in order to mitigate these problems. The research results have proved this strategy was only partially successful as the course of the line and location of the stops do not provide a large number of potential passengers. That is why it was necessary to connect the line to the already existing urban transportation system, yet this solution has not resolved the problem completely. However, the urban development plan assumes introduction of large housing projects in the areas surrounding the existing train stops what will allow using the new line more efficiently in the future.